Considerations in the design and conduct of clinical drug trials in older cancer patients. (May 2012) - Pallis, Athanasios G
The incidence of cancer cases diagnosed in the older population is rising. However, despite this high incidence, several important issues regarding the optimal approach to older cancer patients remains to be elucidated, mostly due to underrepresentation of these patients in clinical trials. The first important issue is associated with the fact that older patients display much greater heterogeneity compared with younger patients. Thus, we need to find reliable tools to discriminate patients who will tolerate treatment and benefit from a standard approach, from others who will experience significant toxicity and will require a more attenuated approach. Another important question is whether clinical trials should have an age-specific design with certain end points or an age-unspecified design. Should we have age-specific trials in all disease settings and for all older patients? In the case of age-specific trials, which is the most appropriate methodology and the most appropriate end point? The purpose of the current article is to discuss the abovementioned issues.